Magnetic Resonance Imaging Conversion Predictors of Clinically Isolated Syndrome to Multiple Sclerosis - Peixoto, Sara (2016)
Introduction: Clinically isolated syndrome may be the first manifestation of multiple sclerosis, a chronic demyelinating disease of the central nervous system, and it is defined by a single clinical episode suggestive of demyelination. However, patients with this syndrome, even with long term follow up, may not develop new symptoms or demyelinating lesions that fulfils multiple sclerosis diagnostic criteria. We reviewed, in clinically isolated syndrome, what are the best magnetic resonance imaging findings that may predict its conversion to multiple sclerosis.Material and Methods: A search was made in the PubMed database for papers published between January 2010 and June 2015 using the following terms: ‘clinically isolated syndrome’, ‘cis’, ‘multiple sclerosis’, ‘magnetic resonance imaging’, ‘magnetic resonance’ and ‘mri’.Results: In this review, the following conventional magnetic resonance imaging abnormalities found in literature were included: lesion load, lesion location, Barkhof’s criteria and brain atrophy related features. The non conventional magnetic resonance imaging techniques studied were double inversion recovery, magnetization transfer imaging, spectroscopy and diffusion tensor imaging.Discussion: The number and location of demyelinating lesions have a clear role in predicting clinically isolated syndrome conversion to multiple sclerosis. On the other hand, more data are needed to confirm the ability to predict this disease development of non conventional techniques and remaining neuroimaging abnormalities.Conclusion: In forthcoming years, in addition to the established predictive value of the above mentioned neuroimaging abnormalities,different clinically isolated syndrome neuroradiological findings may be considered in multiple sclerosis diagnostic criteria and/or change its treatment recommendations.